2002
DOI: 10.1080/01650250042000645
|View full text |Cite
|
Sign up to set email alerts
|

New tools, new insights: Kohlberg’s moral judgement stages revisited

Abstract: In this paper, four sets of data, collected by four different research teams over a period of 30 years are examined. Common item equating, which yielded correlations from .94 to .97 across datasets, was employed to justify pooling the data for a new analysis. Probabilistic conjoint measurement (Rasch analysis) was used to model the results. The detailed analysis of these pooled data con rms results reported in previous research about the ordered acquisition of moral stages and the relationship between moral st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 26 publications
(45 reference statements)
6
74
0
2
Order By: Relevance
“…A recent scaling analysis of 996 moral judgment interviews scored with the Standard Issue Scoring System provided evidence for the specified developmental sequence and some evidence of structured wholeness in development from Moral Stages 3 to 5 (Dawson, 2002b). The instrument did not perform as well at the lower stages as it did at the higher stages.…”
Section: Standard Issue Scoring Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent scaling analysis of 996 moral judgment interviews scored with the Standard Issue Scoring System provided evidence for the specified developmental sequence and some evidence of structured wholeness in development from Moral Stages 3 to 5 (Dawson, 2002b). The instrument did not perform as well at the lower stages as it did at the higher stages.…”
Section: Standard Issue Scoring Systemmentioning
confidence: 99%
“…This meant that development should proceed from one stage to the next in an invariant sequence with no skipping of stages. A large body of longitudinal evidence supports the sequentiality in the acquisition of stages of development (Armon & Dawson, 1997;Case, Okamoto, Henderson, & McKeough, 1993;Colby, Kohlberg, Gibbs, & Lieberman, 1983;Dawson, 2002b;Fischer & Bullock, 1981;Kitchener, King, Wood, & Davison, 1989;Snarey, Reimer, & Kohlberg, 1985;Walker, 1982).…”
mentioning
confidence: 99%
“…As previously mentioned, numerous early validation studies failed to control for variance in moral development scores that could be attributed to education and IQ (Martin, Shaftro, & Van Deinse, 1977). Since these studies, researchers have found a significant association between moral development scores and IQ (Dawson, 2002;Taylor, 1978). In addition, not only do DIT scores increase as the number of years of education increase, but Coder (1975) found that scores increase more with special moral education programs than with non-moral education.…”
Section: Kohlberg's Model Of Moral Developmentmentioning
confidence: 94%
“…Further, in their research assessing moral thinking in a sample aged 14 to 92 years, Pratt, et al found that their participants aged 75 or older showed significantly lower stages of moral development than did their younger participants. Overall, moral reasoning was strongly correlated with age in children, moderately correlated with age in young adults, and education had a significant impact on this relation in each age group (see also Dawson, 2002 …”
Section: Agementioning
confidence: 99%
“…Still other research has found a curvilinear relationship between age and moral philosophy (Pratt, Golding, & Hunter, 1984), with the selection of moral principles that are associated with higher levels of moral development increasing during adolescence and throughout early adulthood (see Armon & Dawson, 1997;Colby & Kohlberg, 1987;Dawson, 2002;Czyzowska & Niemczynski, 1996) and seeming to decrease somewhat in old age (Pratt, Golding, Hunter and Norris, 1988; see also Aldrich & Kage, 2003). Further, in their research assessing moral thinking in a sample aged 14 to 92 years, Pratt, et al found that their participants aged 75 or older showed significantly lower stages of moral development than did their younger participants.…”
Section: Agementioning
confidence: 99%